Evaluation of a robust correlation-based true-speed-over-ground measurement system employing a FMCW radar. Issue 7 (22nd July 2019) - Reissland, Torsten; Lenhart, Bjoern; Lichtblau, Johann; Sporer, Michael; Weigel, Robert; Koelpin, Alexander
Abstract: This paper presents a novel approach for the determination of True-Speed-Over-Ground for trains. Speed determination is accomplished by correlating the received signals of two side-looking radar sensors. The theoretically achievable precision is derived. Test measurements are done in two different scenarios to give a proof of concept. Thereafter a series of field measurements is performed to rate the practical suitability of the approach. The results of the measurements are thoroughly evaluated. The test and field measurements are carried out using a 24 GHz frequency modulated continuous wave radar.